MANAGEMENT OF IT-PROJECTS USING FLEXIBLE METHODOLOGIES AGILE, SCRUM, KANBAN - Fendo , Olena (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The article deals modern methodologies of IT project management are considered, which represent new ways of organizing management activities in order to increase the efficiency of team members’ work and the implementation of project tasks. The advantages and disadvantages of each flexible methodology during their selection for successful project implementation.